PRONOMINA DALAM BAHASA SASAK DIALEK SELAPARANG DI DUSUN MONTONG MEONG - Hubbi Saufan Hilmi; Fabio Testy Ariance Loren (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study aims to describe the shape and use of pronouns in the Sasak dialect of Selaparang. This research uses descriptive qualitative method. The results show that pronouns in Sasak language are divided into three, namely pronouns persona consisting of singular and plural forms, pronoun pointers, and pronouns of the questioner. The use of pronouns in the Sasak dialect of Selaparang in Montong Meong hamlet depends on the social class and the age of the speakers and the opponents of his speech, except the pronouns of the first person plural, the pronouns of the singular and plural third persons, and the pronoun introgative used in all elements of society.